2020
DOI: 10.1891/lgbtq.2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Health of Transgender Women, Transgender Men, and Gender Non-Conforming Individuals Using Population-Level Data

Abstract: Converging evidence indicates transgender and gender non-conforming (TGNC) individuals generally experience poorer health than their cisgender counterparts. Less is known about TGNC health across gender identity subgroups. Extant work has yielded mixed findings, precluding conclusions regarding the comparative health of transgender women, transgender men, and gender non-conforming individuals. Additionally, this work is limited methodologically, e.g., utilizing convenience samples and operationalizing “transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Non-binary is (commonly and in this paper) used as an umbrella term to describe the diverse and nuanced ways individuals experience and identify their genders outside of/not represented by "man/male" or "woman/female" (cis or trans), including, for example, bigender, agender, genderqueer, genderfluid [10,11]. Recent research indicates that non-binary individuals have higher odds of self-reported poor health due to mental or emotional difficulties and are likely to experience more symptoms and worse mental health outcomes compared to binary transgender (i.e., transgender men and women) and cisgender individuals [8,[12][13][14][15][16]. These findings can be interpreted through the lens of minority stress theory [17,18], which proposes that health disparities result from exposure to unique forms of stress, additive to the stress experienced by the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Non-binary is (commonly and in this paper) used as an umbrella term to describe the diverse and nuanced ways individuals experience and identify their genders outside of/not represented by "man/male" or "woman/female" (cis or trans), including, for example, bigender, agender, genderqueer, genderfluid [10,11]. Recent research indicates that non-binary individuals have higher odds of self-reported poor health due to mental or emotional difficulties and are likely to experience more symptoms and worse mental health outcomes compared to binary transgender (i.e., transgender men and women) and cisgender individuals [8,[12][13][14][15][16]. These findings can be interpreted through the lens of minority stress theory [17,18], which proposes that health disparities result from exposure to unique forms of stress, additive to the stress experienced by the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our work adds important nuance to findings about the mental health of nonbinary people, which tends to be grouped with all TGNC students together and indicates poor mental health outcomes (Budge et al, 2013; Downing & Przedworski, 2018; Jones et al, 2019; Lefevor et al, 2019; Lipson et al, 2019; Marshall et al, 2016; Oswalt & Lederer, 2017; Valente et al, 2020). Some previous work has explored the mental health outcomes of nonbinary adults (Guy et al, 2020; Jones et al, 2019), but less work has explored the mental health of nonbinary emerging adults. Future research should explore mental health longitudinally among nonbinary individuals with special attention to the potential improvement of outcomes as they develop coping mechanisms as they reach early and middle adulthood, as is true of their cisgender peers (Diehl et al, 2014; Leipold et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…64 To control for weighting-related sample inflation and potential weight instability in inferential statistics, we multiplied each case's _LLPCWT value by (Unweighted N/Weighted N) to preserve the original N. This approach aligns with recommendations and previous studies. [77][78][79] Missing Data. We assessed data missingness a priori given evidence for data missingness in related studies.…”
Section: Data Preparation and Analytic Planmentioning
confidence: 99%
“…We assessed data missingness a priori given evidence for data missingness in related studies. 77,78 Missingness analyses included Little's Test, univariate missingness, and multivariate missingness patterns. 80 Strategies for handling missingness were chosen based on results from the SPSS Missing Values Analysis module and subsequent literature review.…”
Section: Data Preparation and Analytic Planmentioning
confidence: 99%
See 1 more Smart Citation